Checking the consistency of 3D geological models - M. N. Parquer; E. A. de Kemp; B. Brodaric; M. J. Hillier (Geoscientific Model Development)
Three-dimensional geological modelling algorithms can generate multiple models that fit various mathematical and geometrical constraints. The results, however, are often meaningless to geological experts if the models do not respect accepted geological principles. This is problematic as use of the models is expected for various downstream purposes, such as hazard risk assessment, flow characterization, reservoir estimation, geological storage, or mineral and energy exploration. Verification of the geological reasonableness of such models is therefore important. If implausible models can be identified and eliminated, it will save countless hours and computational and human resources.